Diagnosis and classification of mastocytosis in non‐specialized versus reference centres: a Spanish Network on Mastocytosis (REMA) study on 122 patients. (12th October 2015) - Sánchez‐Muñoz, Laura; Morgado, Jose M.; Álvarez‐Twose, Ivan; Matito, Almudena; Garcia‐Montero, Andrés C.; Teodosio, Cristina; Jara‐Acevedo, Maria; Mayado, Andrea; Mollejo, Manuela; Caldas, Carolina; González de Olano, David; Escribano, Luis; et al.
Summary: The diagnosis of 'rare diseases', such as mastocytosis, remains a challenge. Despite this, the precise benefits of referral of mastocytosis patients to highly specialized reference centres are poorly defined and whether patients should be managed at non‐specialized versus reference centres remains a matter of debate. To evaluate the quality and efficiency of diagnostic procedures performed at the reference centres for mastocytosis in Spain (REMA) versus other non‐reference centres, we retrospectively analysed a series of 122 patients, for the overall degree of agreement obtained for the World Health Organization (WHO) diagnostic and classification criteria betwen the referring and REMA centres. Our results showed that not all WHO diagnostic criteria were frequently investigated at the referring centres. Among the five WHO diagnostic criteria, the highest degree of agreement was obtained for serum tryptase levels [median 90% (95% confidence interval 84–96%)]; in turn, the overall agreement was significantly lower for the major histopathological criterion [80% (72–89%)], and the other three minor criteria: cytomorphology [68% (56–80%)] immunophenotyping of BM mast cells [75% (62–87%)] and detection of the KIT mutation [34% (8–60%)]. Referral of patients with diagnostic suspicion of mastocytosis to a multidisciplinary reference centre improves diagnostic efficiency and quality.